Hearing the puzzle: The inner ear evolution of Platanistoidea (Cetacea: Odontoceti) - Viglino, Mariana (2021)
Hearing is one of the key senses for modern cetaceans (Neoceti) to hunting and communication, adapted for either infrasonic (Mysticeti) or ultrasonic (Odontoceti) frequencies. Among odontocetes, the Platanistoidea comprises a single extant riverine representative (Platanista gangetica) but numerous extinct marine species from the late Oligocene onward. Platanista is a critically endangered odontocete species that possess unique morphological characteristics, but their evolutionary patterns remain mostly unknown. Studying extinct platanistoids' hearing abilities might contribute a piece to the complex evolutionary puzzle of this group to understand its drastic diversity reduction. Thus, we describe for the first time the inner ear morphology of 6 late Oligocene–early Miocene extinct marine platanistoids from New Zealand and Patagonia (Argentina).